Theologische Auseinandersetzungen in der liturgischen Arbeit in der dänischen Kirche - Glenthøj, Jørgen (Jahrbuch für Liturgik und Hymnologie, 1984)
The author explains with many examples the theological and practical developments in the worship of the Danish Protestant Church over the last two decades. Over against the prevailing 'destructive' theological concept of a liturgy for the whole Danish people he holds up an impressive Eucharistic concept for the future worship of the Danish Church.